An Empirical Study of the Career Paths of Senior Educational Administrators in Manitoba, Canada: Implications for career development - Wallin, Dawn (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
This paper conceptualizes queue theory (Tallerico & Blount, 2004) to discuss a mixed-methods study that determined the career patterns of senior educational administrators in public school divisions in Manitoba, Canada, compared by position, context and sex. Findings indicate that queue theory has merit for describing the career paths of senior administrators in Manitoba, but it must be qualified. Context creates labour queue stratifications based on educational level (access), the extent to which senior administrators are channeled into traditional career paths, and number of positions served overall. Context, sex and position interact to form queues based on leaves from service, and create discrepancies on the experiences of career supports and work challenges.